Small Sided Games Training Model to Improve Basic First Touch Football Technical Skills of Football School Students - Putra, Aldo Naza; Edmizal, Eval; Wulandari, Indri; Amra, Frizki; Atradinal; Zarya, Fiky; Munir, Ali (Journal for Lesson and Learning Studies, 2024)
Training modification is an important strategy in sports training to improve athlete performance, and in the context of football, SSG is one promising method. Therefore, this study aims to analyze the effectiveness of the Small Sided Games (SSG) training model in improving basic football technique skills in Muspan U-12 Year Football School (SSB) students. This study used a quantitative approach with Quasi-Experimental method, adopting Pre-test Post-test Non-Equivalent Control Group design to measure exercise effectiveness. The sample of this study consisted of SSB Muspan U-12 Year students. Data was collected through tests that measured basic football technical skills, namely passing, dribbling, and shooting. This test is carried out before and after the application of the SSG exercise model, to assess changes in basic engineering skills. The results of the data analysis showed a significant improvement in basic football technical skills after the implementation of SSG training. This is evidenced by the sig (2-tailed) value of the Independent Sample t-Test test which reaches 0.000, far below the threshold of 0.05. These findings confirm that SSG practice is effective in improving basic football technique skills in SSB Muspan U-12 Year students. The conclusions of this study are important for football coaches working with younger age groups, suggesting that exercise modification through the SSG model can be an effective strategy for improving basic technical skills.